Promoting Diversity through Multilevel Activism: An Organizational Approach - Patricia Alvarez McHatton; Barbara J. Shircliffe; Deirde Cobb-Roberts (Educational Considerations, 2011)
The National Council for Accreditation of Teacher Education (NCATE) was founded in 1954 to serve as an independent body in promoting high quality teacher preparation programs.
Keywords: College; education; diversity; sustainable; program; committee; NCATE; student; recruitment; retention; resource